Influence of nonviable lactobacillus fermentation product in artificially reared pigs challenged with e. coli - Pollmann, D.S.; Kennedy, G.A.; Koch, B.A.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to determine the influence of non viable lactobacillus fermentation product (LFP) in artificially reared pigs removed from sows at 24 to 36 hours postpartum. The pigs were fed a non-medicated milk replacer for 21 days in individual cages in an environmentally controlled room. In Trial I, 5 levels (0, .25, .5, 1.0, and 2.0 ml per pig per day) of LFP were used to determine the dosage rate on growth, feed efficiency, mortality rate, white blood cell count, and hematocrit (8 pigs per treatment). No detectable dosage rate was obvserved in Trial I. In Trial II, a study was conducted to determine the effect of LFP on lactobacill us and coli form (E. coli) counts, histopathology of the small intestine, growth and blood parameters. When pigs were 14 days old they received an inoculum of either a broth containing E. coli (strain K88,91; approximately billion organisms for two days) or broth without E. coli. Pigs were fed three levels of the LFP at 0, .5, and 1.0 ml per day. Pigs were sacrificed five days and seven sections of gastrointestinal tract and feces were excised to enumerate lactobacillus and coliform populations. A dose rate of .5 ml per day increased gain (P<.08) and suppressed E. coli count in the stomach area without affecting lactobacillus populations.- No differences were detected with the pathological evaluation. By challenging the pigs with E. coli, jejunum (section of the small intestine) coliform and white blood cell counts were increased (P<.06). These results suggest that lactobacillus fermentation product suppresses E. coli counts in the stomach and may improve gain in the artificially reared pig.
Keywords: Swine; Nonviable lactobacillus fermentation; E.coli